The role of catalyst environment on CO2 hydrogenation in a fixed-bed reactor. (January 2017) - Bradley, Matthew J.; Ananth, Ramagopal; Willauer, Heather D.; Baldwin, Jeffrey W.; Hardy, Dennis R.; DiMascio, Felice; Williams, Frederick W.
Graphical abstract: CO2 hydrogenation using iron-based catalyst coated in start-up solvent. Highlights: Startup solvent was added to CO2 hydrogenation catalyst reactions in a fixed-bed reactor at different temperatures. Thorough characterization of the catalyst found that the solvent decreased catalyst oxidation. Computational and kinetic analysis indicated solvent decreased catalyst oxidation by suppressing water adsorption onto the catalyst surface. Abstract: To reduce the negative impact that water formation has on the catalyst environment during CO2 hydrogenation reactions in a fixed-bed reactor, a start-up solvent, (mineral oil) was added to the reactor as a pretreatment. A Macrolite ® -supported iron-based catalyst was used as the model catalyst to determine the impact of pretreatment with mineral oil on product selectivity, CO2 conversion, and catalyst stability over a range of reaction temperatures (280 °C, 300 °C, and 320 °C). At the lower reaction temperatures (280 °C, 300 °C), CO2 conversion and C2-C5+ yield was increased by as much as 17% and 25% respectively by addition of start-up solvent. The characterization of the catalyst showed the formation of an iron manganese oxide phase, in the absence of the start-up solvent. Modeling and kinetic analysis of the data suggested that the start-up solvent decreased oxidation of the catalyst phase by reducing water adsorption, thereby increasing the Fischer-Tropsch reaction rate. This led to an increase in hydrocarbon yield in the presence of mineral oil.